Impact of Translation Techniques and Ideology Quality Text Translation in Mantra Jamuan Laut - Dewi Kesuma Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Mantra Jamuan Laut is spells or words used by a sea-handler in the process of Ritual Ceremony among Malay society in Kabupaten Serdang Bedagai, North Sumatra - Indonesia. This study deals with translation technique, ideologies and quality of the translated text of sea repast incantation from Malay language into English. There was 82 clauses of translated text as the data. The source of data is the utterances of a sea-handler and FGD. Descriptive qualitative was applied by using Molina and Albir’s theory to find out the translation techniques meanwhile the theory of Nababan & Machali used to figure out the quality of the translation. Considering the fact that the data which consists of four incantations are translated by five translators, then the results of their translation vary. From the analysis, it was found that there were 11 techniques of 18 applied with literal as the most dominant technique. Thereby the translators embraced foreignization ideology that mainly focuses on the source text. The utilization of foreignization ideology and the use of source language-oriented translation techniques showed that intercultural and thematic knowledge of the translators are insufficient. Since the frequency of literal technique was less than 25%, the quality of translated-text was regarded as ‘fair’.